Supervisors' perceptions on errors of nursing students in clinical clerkship: a qualitative research - Ana Paula Sousa Santos; Márcio Filipe Moniz Tavares; Alberto Carlos Marques Duarte; Fábio Alexandre Melo do Rego Sousa
ABSTRACT Objectives: to compare pedagogical supervisors' and clinical supervisors' perceptions about the errors made by nursing students in clinical clerkship. Methods: a qualitative exploratory-descriptive study developed with 105 participants. Data collection was performed with a questionnaire with open-ended questions. Content analysis performed according to the conceptual model of student errors in clinical teaching. Results: pedagogical supervisors perceive, in descending order, errors in transversal competencies, in the execution of care and medication. Clinical supervisors perceive, in descending order, the execution of care, medication, and transversal competencies. Final Considerations: there was coincidence and complementarity in clinical supervisors' and pedagogical supervisors' perceptions, although not in the same order, regarding the errors made. This study presents contributions related to the existing knowledge in relation to medication errors, which are not the most perceived, and those of transversal competencies, which take on a prominent position.